A house among the trees [large type] - Glass, Julia, 1956- (Center Point Large Print, 2017)
"When the revered children's book author Mort Lear dies accidentally at his Connecticut home, he leaves his property and all its contents to his trusted assistant, Tomasina Daulair, who is moved by his generosity but dismayed by the complicated and defiant directives in his will"--